The effect of SARS-CoV-2 Omicron BA. 5.2 infection on perioperative physiological indicators in orthopedic patients - Hao Wu; JunZhe Yang; YuQin Yan; Xiao Hu; BiXi Li; PengFei Cheng; XiaoYang Song (BMC Musculoskeletal Disorders)
Abstract Objective The aim of this study was to investigate the effect of SARS-CoV-2 Omicron BA. 5.2 (hereafter referred to as Omicron BA. 5.2) infection on perioperative physiological indices and to provide clinical considerations for the precautions needed for patients who tested negative for SARS-CoV-2 infection perioperatively. Methods Patients who underwent time-limited surgery (surgery that must be performed within a certain time) at the Department of Orthopedics of our hospital from September 1, 2022, to March 31, 2023, were divided into an observation group (those with Omicron BA 5.2 and a negative nucleic acid test after December 7, 2022, n = 100) and a control group (those negative for SARS-CoV-2 infection before December 7, 2022, n = 100). Changes in the following factors were compared within and between the two groups: heart rate, mean arterial pressure, oxygenation index at the time of entry into the operating room, incision of the skin and exit from the operating room and the neutrophil‒lymphocyte ratio (NLR), platelet‒lymphocyte ratio (PLR), systemic immune inflammation index (SII), D-dimer level, and fibrinogen degradation product (FDP) level. Changes in interleukin-6 and calcitonin levels were assessed the day after surgery, and multivariate regression analysis of the meaningful results was conducted. Results Heart rate, mean arterial pressure, oxygenation index, NLR, PLR, SII, interleukin-6 and calcitonin were similar between the two groups (P > 0.05). The observation group had higher postoperative D-dimer and FDP levels (P < 0.05). Multivariate regression analysis revealed that Omicron BA 5.2 infection, older age and a history of cerebral infarction were associated with increased D-dimer and FDP levels, and their odds ratios (ORs) and confidence intervals are 3.339 [95% CI, 1.372–8.419], P = 0.008; OR, 1.080 [95% CI, 1.023–1.139]; P = 0.005; OR, 10.644 [95% CI, 1.352–83.320], P = 0.025, respectively. Conclusion Omicron BA. 5.2 Infection affects the perioperative coagulation function of orthopedic patients, thereby inducing a hypercoagulable state characterized by significant elevations in D-dimer and FDP levels and increasing the risk of venous thrombosis. This infection had no obvious effect on other physiological indices. Early surgery is feasible, but thrombotic events need to be considered.